Agricultural terminology - Dhaka, S.R....et.al.; Jat, R.A; Kantwa, S.R.; Dhaka, B.L. (New Delhi : New Vishal Publication, 2012)
This dictionary is written to provide a useful reference source for all those have interest in agriculture in whatever capacity. It is collection and compilation work from various sources like books, journal and monographs etc. It has been endeavoured to include as many terms as could be possible. No efforts have been spared to make it as comprehensive as could be done. Some of the terms have been lengthy to define the important aspects. It may be made very clear that this compilation is neither adequately comprehensive nor complete.
Keywords: Agriculture-Terminology